Study of space weather impact on Antarctica ionosphere from GNNS data - Bergeot, Nicolas; Chevalier, J.-M.; Bruyninx, Carine; Denis, G.; Camelbeeck, Thierry; VAN DAM, Tonie; FRANCIS, Olivier (2016)
The impact of solar activity on the ionosphere at polar latitudes is not well known compare to low and mid-latitudes due to lack of experimental observations, especially over Antarctica. Consequently, one of the present challenges of the Space Weather community is to better characterize (1) the climatological behavior of the polar ionosphere in response to variations of the solar activity and (2) the different response of the ionosphere at high latitudes during extreme solar events and geomagnetic storms. For that, the combination of GNSS measurements (e.g. GPS, GLONASS and Galileo) on two separate frequencies allows determining the ionospheric delay between a ground receiver and a satellite. This delay is function of the integrated number of electrons encountered in the ionosphere along the signal ray path, called the Total Electron Content (TEC). It is thus possible to study the behavior of ionospheric TEC at different time and spatial scales from the observations of a network of permanent GNSS stations. In the frame of GIANT-LISSA and IceCon projects we installed since 2009 five GNSS stations around the Princess Elisabeth station. We used these stations additionally to other stations from the IGS global network to estimate the ionospheric TEC at different locations over Antarctica. This study presents this regional data set during different solar activity levels and discusses the different climatological behaviors identified in the ionosphere at these high latitudes. Finally, we will show few examples of typical TEC disturbances observed during extreme solar events.